2020
DOI: 10.2217/fca-2020-0121
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Left Ventricular Global Longitudinal Strain By Speckle Tracking Echocardiography in COVID-19 Patients

Abstract: COVID-19 infection can affect the cardiovascular system. We sought to determine if left ventricular global longitudinal strain (LVGLS) is affected by COVID-19 and if this has prognostic implications. Materials & methods: Retrospective study, with LVGLS was measured in 58 COVID-19 patients. Patients discharged were compared with those who died. Results: The mean LV ejection fraction (LVEF) and LVGLS for the cohort was 52.1 and -12.9 ± 4.0%, respectively. Among 30 patients with preserved LVEF(>50%), LVGLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 23 publications
5
46
1
2
Order By: Relevance
“…These abovementioned findings were similar with the results of our study. Different from our study, Krishnamoorthy et al reported right ventricular dysfunction in 41.7% of the patients and left ventricular dysfunction in 58.3% via using two-dimensional speckle-tracking echocardiography [ 39 ]. It was found that right ventricular longitudinal strain was a strong predictor of mortality in COVID-19 patients [ 40 ].…”
Section: Discussioncontrasting
confidence: 91%
“…These abovementioned findings were similar with the results of our study. Different from our study, Krishnamoorthy et al reported right ventricular dysfunction in 41.7% of the patients and left ventricular dysfunction in 58.3% via using two-dimensional speckle-tracking echocardiography [ 39 ]. It was found that right ventricular longitudinal strain was a strong predictor of mortality in COVID-19 patients [ 40 ].…”
Section: Discussioncontrasting
confidence: 91%
“…Li et al found that RV-LS at − 23% cutoff was associated with AUC 0.87, sensitivity of 94.4%, and specificity of 64.7% [8]. Croft et al reported that LV-GLS reduction of > 8.5 showed trend towards increased mortality, but was not independently associated; the unadjusted or adjusted ratio and their corresponding p values were not thoroughly reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…Three full-text articles were excluded because (1) comparison was between cardiac vs non-cardiac injury (n = 1); (2) comparison was between COVID-19 (+) vs COVID-19 (-) (n = 1); and (3) case series with inadequate comparison (n = 1). There were seven studies comprising of 612 patients in the qualitative and quantitative synthesis [4,[6][7][8][15][16][17]. The baseline characteristics of the included studies are displayed in Table 1.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In COVID-19 patients, a limited number of echocardiographic evaluations have been done with speckle tracking [ 7 9 ]. These evaluations have reported a frequent decrease in right and left ventricular GLS, but they did not provide any comparison with classic indices of systolic function.…”
mentioning
confidence: 99%